Pengaruh Inflasi, BI-7 Day Reverse Repo Rate, Kurs, Jumlah Uang Beredar dan Indeks Harga Saham Gabungan terhadap Nilai Aktiva Bersih Reksa Dana Saham - Jhon Lismart Benget. P. (Politeknik Ganesha Medan, 2021)
The purpose of this study is to examine the effect of inflation, BI-7 day reverses repo rate, exchange rate, the money supply, and composite stock price index on the net asset value of stock mutual funds. The population of this study is the stock mutual fund which was listed on the financial services authority in 2017-2020. The results of this study indicate that simultaneously inflation, BI-7 day reverse repo rate, exchange rate, the money supply, and composite stock price index affect the net asset value of the stock mutual fund. Partially, this study show BI-7 day reverse repo rate has a positive and significant effect on the net asset value of a stock mutual fund. The exchange rate has a positive and significant effect on the net asset value of stock mutual funds. The composite stock price index has a positive and significant effect on the net asset value of stock mutual funds. The money supply has a negative and significant effect on the net asset value of a stock mutual fund while inflation has no significant effect on the net asset value of a stock mutual fund.